Advanced characterisation of 3D structure and porosity of ordinary portland cement (OPC) mortar using plasma focused ion beam tomography and X‐ray computed tomography. (19th April 2022) - Dong, Peng; Yuan, Hui; Allahverdi, Ali; Raveenthiran, Jatheeshan; Piché, Nicolas; Provencher, Benjamin; Bassim, Nabil D.
Abstract: The visualisation and quantification of pore networks and main phases have been critical research topics in cementitious materials as many critical mechanical and chemical properties and infrastructure reliability rely on these 3D characteristics. In this study, we realised the mesoscale serial sectioning and analysis up to ∼80 μm by ∼90 μm by ∼60 μm on portland cement mortar using plasma focused ion beam (PFIB) for the first time. The workflow of working with mortar and PFIB was established applying a prepositioned hard silicon mask to reduce curtaining. Segmentation with minimal human interference was performed using a trained neural network, in which multiple types of segmentation models were compared. Combining PFIB analysis at microscale with X‐ray micro‐computed tomography, the analysis of capillary pores and air voids ranging from hundreds of nanometres (nm) to millimetres (mm) can be conducted. The volume fraction of large capillary pores and air voids are 11.5% and 12.7%, respectively. Moreover, the skeletonisation of connected capillary pores clearly shows fluid transport pathways, which is a key factor determining durability performance of concrete in aggressive environments. Another interesting aspect of the FIB tomography is the reconstruction of anhydrous phases, which could enable direct study of hydration kinetics of individual cement phases.